Condição corporal de aves em fragmento de mata estacional semidecidual do Triângulo Mineiro, Brasil - Teles, Daniella Reis Fernandes (2013)
Body condition has effect on fitness of the birds, being the Body Index (IMR) a tool for indirect estimation of nutritional reserves. The aim of this work was to evaluate how factors such as feeding guilds, seasons, ectoparasitism and subcutaneous fat has interfered on birds IMR. There were made both, general analysis of all the captured individuals, and species analysis (with at least five individuals captured each season). Was also accomplished a monthly estimation of the feed resources offerings (fruits and arthropods). The birds were captured (N = 410) with mist nets, weighed and measured on a fragment of the semidecidual forest of Cerrado. The estimation of fruits offering, was monthly made through the reproductive fenology of individuals (N = 82) of six species of plant from understory, which presented a large fructification on the dry season. The monthly estimation of arthropods was made by using three traps (pitfall, pan-trap and entomological umbrella). The monthly biomass (dry weight) of arthropods was larger during the rainy season. On the general analysis of the birds collected, the IMR has varied: amongst the feeding guild (larger between the omnivore and inferior between the insectivores); between dry and wet season (larger in the dry season) and between the levels of subcutaneous fat (larger to the level 4). Only ectoparasitism did not have significative difference between the mites and ticks parasitized and not parasitized individuals. In the analysis by species, were considered Antilophia galeata, Arremon flavirostris, Basileuterus hypoleucus, Basileuterus leucophrys, Lanio penicillatus e Tolmomyias sulphurescens. Differently from what was found in the general analysis, the IMR has varied only for the ectoparasitism. Tolmomyias sulphurescens had negatively affected the IMR by the presence of ticks and Antilophia galeata by the presence of mites. The semidecidual forest of this study has shown itself stable regarding to the offering of feed resources, and may have contributed for the birds general IMR to be larger during the dry season, not having presented seasonality for the species. The scarcity of studies on the Cerrado and many other brazilian biomes that relates the IMR with physiological variables (subcutaneous fat and ectoparasitism) and environmental (availability resources and climatic seasonality) obstructs the comparing of these results with other bird communities.